Consequências da violação da simetria de Lorentz no Efeito Casimir - Ullio, Ícaro Joshua Morales (2015)
In this Dissertation we’ll consider a scalar field theory where the breaking of Lorentz symmetry is present. Basically we will adopt the Ho˘rava-Lifshtz theory. We’ll study the modifications that an anisotropy in space-time produces in the Casimir effect. Let’s deal with a massless real scalar field in two distinct situations: between parallel plates and inside a two-dimensional rectangular box. In both cases we will adopt specific boundary conditions on the field. As we shall see, the Casimir energy and force strongly depends on the parameter associated with the breaking of Lorentz symmetry.